EPIDEMIOLOGICAL CHARACTERISTICS AND ASSOCIATED FACTORS OF DERMATOPHYTOSIS AMONG PATIENTS AT CAN THO UNIVERSITY OF MEDICINE AND PHARMACY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To describe epidemiological characteristics and identify factors associated with dermatophytosis among patients at Can Tho University of Medicine and Pharmacy Hospital.Methods: A cross-sectional study was conducted. Dermatophytosis was diagnosed using direct microscopy and culture on Dermatophytes Test Agar. Epidemiological characteristics and potential associated factors were collected using a structured questionnaire. Multivariable logistic regression analysis was performed to identify independent associated factors.Results: The prevalence of dermatophytosis among patients with suspected fungal skin lesions was 26%. Patients aged ≥ 60 years had a significantly higher prevalence compared with those aged
Keywords: Dermatophytosis, prevalence, risk factors